THE EFFECTIVENESS OF LAVENDER AROMATHERAPY IN CHANGING BLOOD PRESSURE IN MIDDLE AGE WITH PRIMARY HYPERTENSION IN MOJOKERTO REGENCY OF EAST JAVA PROVINCE - Suidah, Hartin; Murtiyani, Ninik Murtiyani; Fibriana, Linda Presti; Lestari, Yufi Aris; Kushayati, Nuris (Advances in Social Sciences Research Journal, 2018)
THE EFFECTIVENESS OF LAVENDER AROMATHERAPY IN CHANGING BLOOD PRESSURE IN MIDDLE AGE WITH PRIMARY HYPERTENSION IN MOJOKERTO REGENCY OF EAST JAVA PROVINCE Authors: Hartin Suidah(1), Ninik Murtiyani(2),Linda Presti Fibriana(3), Nuris Kushayati(4), Yufi Aris Lestari(5) (1,2,3,4) DIAN HUSADA NURSING ACADEMY OF MOJOKERTO, EAST JAVA, (5)HIGH SCHOOL OF HEALTH SCIENCES DIAN HUSADA OF MOJOKERTO, EAST JAVA ABSTRACT Background: In 2010, hypertension case becomes one out of 10 most prevalent diseases in Indonesia with the prevalence of 8.24%: 3.49% in male and 4.75% in female [8]. The research was to analyze the effectiveness of lavender aromatherapy in changing blood pressure in middle age with primary hypertension. Method: This research employed Quasi-Experiment method with control group time series design. The sample of research consisted of 32 respondents taken using probability sampling with simple random technique. Data analysis was conducted based on data tabulation with paired T-test with α = 0.05. Result: After lavender aromatherapy was given or 7 days, the average respondent decreased blood pressure gradually to the level of normal blood pressure. The result of paired T-test obtained significance level p = 0.008 or less than α = 0.05. Conclusion: Lavender aromatherapy effectively changed the blood pressure in middle age with primary hypertension. Keywords: Lavender Aromatherapy, Primary Hypertension, Blood Pressure, Middle Age